A novel test for the presence of local explosive dynamics - Francisco Blasques; Siem Jan Koopman; Gabriele Mingoli; Sean Telg (Tinbergen Institute, 2024)
In economics and finance, speculative bubbles take the form of locally explosive dynamics that eventually collapse. We propose a test for the presence of speculative bubbles in the context of mixed causal-noncausal autoregressive processes. The test exploits the fact that bubbles are anticipative, that is, they are generated by an extreme shock in the forwardlooking dynamics. In particular, the test uses both path level deviations and growth rates to assess the presence of a bubble of given duration and size, at any moment of time. We show that the distribution of the test statistic can be either analytically determined or numerically approximated, depending on the error distribution. Size and power properties of the test are analyzed in controlled Monte Carlo experiments. An empirical application is presented for a monthly oil price index. It demonstrates the ability of the test to detect bubbles and to provide valuable insights in terms of risk assessments in the spirit of Value-at-Risk.
Keywords: C22; E31; E37; 330; noncausality; bubbles; testing; date-stamping; risk assessment